2015
DOI: 10.2174/1874325001509010542
|View full text |Cite
|
Sign up to set email alerts
|

The Lateral Meniscus as a Guide to Anatomical Tibial Tunnel Placement During Anterior Cruciate Ligament Reconstruction

Abstract: Purpose: The aim of the study is to show, on an MRI scan, that the posterior border of the anterior horn of the lateral meniscus (AHLM) could guide tibial tunnel position in the sagittal plane and provide anatomical graft position.Method:One hundred MRI scans were analysed with normal cruciate ligaments and no evidence of meniscal injury. We measured the distance between the posterior border of the AHLM and the midpoint of the ACL by superimposing sagittal images.Results:The mean distance between the posterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Using the root ligament of the AHLM as a radiologic reference point on MRI is supported in the literature, which describes this structure as being a reliable and reproducible landmark. 10 Kassam et al 10 recently demonstrated that the ACL tibial footprint was on average 0.1 mm anterior to the posterior border of the AHLM. Zantop et al 27 showed that the center of the AM bundle is aligned with the AHLM in cadaveric specimens.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using the root ligament of the AHLM as a radiologic reference point on MRI is supported in the literature, which describes this structure as being a reliable and reproducible landmark. 10 Kassam et al 10 recently demonstrated that the ACL tibial footprint was on average 0.1 mm anterior to the posterior border of the AHLM. Zantop et al 27 showed that the center of the AM bundle is aligned with the AHLM in cadaveric specimens.…”
Section: Discussionmentioning
confidence: 99%
“…The reference point chosen was the center point of the root ligament of the AHLM, which is a reproducible landmark and easily visualized on axial and sagittal plane MRI. 10 For the ACL footprint, we identified the center point of the entire ACL footprint, which included both the anteromedial (AM) and posterolateral (PL) bundles. Next, we superimposed both axial images and measured the distance from the center point of the ACL footprint to the center point of the root ligament of the AHLM in the coronal (medial-lateral) and sagittal (anterior-posterior) planes (see Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PBAHLM can be up to 5 mm from the center of the ACL footprint; thus careful correlation of the position of the PBAHLM and the center of the ACL footprint is recommended preoperatively, on an MRI scan, and intraoperatively to ensure the tibial tunnel is placed in an anatomic position. 9 Consideration must be taken when the planned position of the tunnel is too anterior and a surgical decision needs to be made to avoid tunnel placement too anteriorly to prevent graft impingement. Preoperatively, the position of the PBAHLM should be assessed in relation to the center of the ACL footprint on an MRI scan.…”
Section: Discussionmentioning
confidence: 99%